Analysis and Modelling of Ultrasonic Pulses in a Biological Medium - OPIELIŃSKI, Krzysztof J. (Archives of Acoustics, 2008)
In this work, formulas were presented, which allow modelling of linear and nonlinearpropagation of ultrasonic wave in a biological medium, by simulating the shape of pulseswhich propagate in this medium. Analysed and measured in chosen biological media usingtransmission method, the linear and nonlinear ultrasonic pulses were modelled by means ofdeveloped formulas. Very good compatibility of the representation was achieved both in thearea of time and frequency. In case of biological media causing high attenuation of ultrasonicwave, reduction of mid frequency in the receiving pulse caused by attenuation dispersion wasobserved.